Induced expression of Ganoderma boninense lanosterol 14α-demethylase (ERG11) during interaction with oil palm - Lim, Fook-Hwa; Abd Rasid, Omar; Abu Seman, Idris; Abdul Wahab, Mohd As’wad; Vadamalai, Ganesan; Ahmad Parveez, Ghulam Kadir; Wong, Mui-Yun (Springer, 2023)
Background: The basidiomycete fungus, Ganoderma boninense is the main contributor to oil palm Basal Stem Rot (BSR) in Malaysia and Indonesia. Lanosterol 14α-Demethylase (ERG11) is a key enzyme involved in biosynthesis of ergosterol, which is an important component in the fungal cell membrane. The Azole group fungicides are effective against pathogenic fungi including G. boninense by inhibiting the ERG11 activity. However, the work on molecular characterization of G. boninense ERG11 is still unavailable today. Methods and results: This study aimed to isolate and characterize the full-length cDNA encoding ERG11 from G. boninense. The G. boninense ERG11 gene expression during interaction with oil palm was also studied. A full-length 1860 bp cDNA encoding ERG11 was successfully isolated from G. boninense. The G. boninense ERG11 shared 91% similarity to ERG11 from other basidiomycete fungi. The protein structure homology modeling of GbERG11 was analyzed using the SWISS-MODEL workspace. Southern blot and genome data analyses showed that there is only a single copy of ERG11 gene in the G. boninense genome. Based on the in-vitro inoculation study, the ERG11 gene expression in G. boninense has shown almost 2-fold upregulation with the presence of oil palm. Conclusion: This study provided molecular information and characterization study on the G. boninense ERG11 and this knowledge could be used to design effective control measures to tackle the BSR disease of oil palm.